AND WHAT I DON'T LIKE ABOUT YOU... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
At a United Nations conference on 'Building Partnerships' in September 1997, the then Chairman of the UN General Assembly, Ambassador Razali Ismail addressed the issues of the 'non-transparency of how NGOs are structured and organised, their tunnel...